Peran Kejelasan Regulasi Organisasi Dan Kepemimpinan Transformasional Dalam Membentuk Disiplin Kerja Karyawan Dengan Pendekatan Logico Dan Verifikatif - Rivaldi Ramadhan; Muhardi (STIM-LPI Makassar, 2026)
This study aims to analyze the role of organizational regulatory clarity and transformational leadership in shaping employee work discipline using a logical approach through the Systematic Literature Review (SLR) method. Employee work discipline is a fundamental element in maintaining organizational effectiveness, stability, and sustainability. However, in practice, work discipline is often influenced by unclear internal regulations and weak leadership roles in instilling organizational values and norms. The research method involves a systematic review of reputable national and international journal articles as well as academic books relevant to organizational regulation, transformational leadership, and employee work discipline. The SLR process includes identification, selection, quality assessment, and synthesis of the literature based on a rational and systematic logical framework. The findings indicate that organizational regulatory clarity serves as a normative foundation that provides behavioral certainty and enhances employee compliance, while transformational leadership plays a critical role in internalizing disciplinary values through role modeling, motivation, and inspiration. The integration of these two factors is proven to strengthen sustainable employee work discipline. This study concludes that work discipline is shaped not only by formal rules but also by leadership quality that effectively translates regulations into meaningful work behavior.